Digital Evidence Nature:its Role in enhancing judge’s Convincing - Juma, Ass.Lec Abbas Ibrahim (Thi Qar Arts Journal, 2022)
The rate of impunity for perpetrators the information’s crimes to be brought to the courts for trial is very large because of the inability of the judicial authorities to reach the proof of the commission of this type of crime. As well as, identifying the perpetrators of the perpetrators, because of not dealing with evidence of proof of this type of crimes on As it is characterized by its specificity. This prompted us to research the merits of the digital evidence and identify the characteristics that must be paid attention to, as well as the defects that distinguish it from the evidence in traditional crimes.